Diagnosa Gangguan Signal Smartphone Android Dengan Sistem on Chip(SoC) Snapdragon Menggunakan Metode Forward Chaining - Fadli Fadilillah; Faisal Amir; Rajimar Suhal Hasibuan; Riyanto Riyanto; Fadhilah Oriyasmi (JURTEII: Jurnal Teknologi Informasi, 2023)
Signal interference can also occur on official smartphones circulating in Indonesia. it is common for a smartphone to have a weak signal so that the smartphone cannot get a signal from the provider used without any incident. The need for analysis of signal interference that occurs on smartphones to find out the causes and solutions in handling signal interference is considered very appropriate to overcome this problem. Moreover, the solutions and information provided are based on experts or people who are experts in the field of Smartphone repair. Forward Chaining is a method of the Inference Engine to start reasoning and tracking from existing facts to a conclusion. So that the diagnosis of Android smartphone signal interference with Snapdragon SoC using the Forward Chaining Method is considered very appropriate for analyzing problems and providing information and solutions to Android users and Beginner Cellphone repair technicians.